G242 A survey exploring attitudes, skills and willingness of paediatric trainees to manage children and young people with acute mental health presentations in secondary care. (May 2019) - Wooding, EL; Mason, T; Conn, R
Abstract : Children and young people (CYP) increasingly present to hospital with complicated emotional and/or behavioural problems. Professionals, including paediatricians may feel poorly prepared to manage these patients well, impacting patient experience. We aimed to explore knowledge and attitudes around mental health management in our region amongst paediatric trainees. This project supported a multicentre audit assessing mental health admissions to paediatric units. Methods: A digital survey was created by members of a regional paediatric trainee research collaborative alongside local stakeholders. Data was collected on trainee grade, mental health training, training needs and perceived confidence and competence in this area. Questions were a mixture of 5-point Likert scales, free text and multiple-choice questions. The survey was circulated to all paediatric trainees regionally via official channels. Results: Of the 44 respondents to the survey 1 had received formal training in mental health risk assessment during paediatric training. 66% of participants considered the paediatric service to CYP presenting with mental health issues to be poor or very poor (1–2/5 on Likert scale). 7% felt confident (4+on Likert scale) risk-assessing CYP for discharge; 23% would perform this role if adequately trained and supported. 27% had a psychosocial meeting with psychiatry support in their locality. 93% of trainees were interested in linking with CAMHS trainees further to improve knowledge and understanding. Conclusion: The majority of respondents felt that the service received by CYP from paediatrics was sub-optimal. More promisingly, there is enthusiasm for greater collaboration, training and understanding of mental health presentations, risk assessment and management amongst these trainees. Trainees were keen to broaden their experience and competence in risk assessment with a view to discharging patients, with appropriate support. The vast majority of respondents were keen to explore options for closer CAMHS/paediatric collaboration to share knowledge and understanding. Following this survey a mental health study day for registrars has been added to the regional programme, with further options to develop training, including a SPIN module in mental health being explored.